A study of Cognitive Domains on Cooperative and Collaborative Learning A case of exhibition and museum design course - Kernsom, Thitipann (Asian Creative Architecture, Art and Design, 2022)
The objectives of this research were 1) to develop the teaching and learning process according to the collaborative learning strategy of cooperative and collaborative learning through projects of undergraduate students in the Exhibition and Museum Design Course 2) to study the learning achievements of the exhibition and museum design course with a cooperative and collaborative learning strategy with collaborative learning through project works of undergraduate students by giving learners an average academic achievement score of not less than 75% 3) to study student satisfaction through a cooperative and collaborative learning strategy with collaborative learning through the project results of undergraduate students by giving students a level of satisfaction of not less than 3.5. 4) assessed students' satisfaction in the exhibition and museum design courses. Forty-nine samples included in this research were undergraduate students of the researcher’s workplace, the first semester of 2020 with purposive sampling. The research tools were 1) a lesson plan for exhibition and museum design courses that organized cooperative and collaborative learning activities through 4 project works, 2) scoring rubric with evaluating form, 3) cognitive learning achievement score form, 4) satisfaction assessment form. The research results found that 1) the effects of cooperative and collaborative learning activities through project resulted in students' understanding, analytical thinking, and ability to solve the problem. This data created a body of knowledge and influenced the teachers to know the issues, challenges in teaching and learning, and solutions. 2) the evaluation results of the cooperative and collaborative learning activities through the project revealed that the learners could do projects according to their interests, stimulating interest, and taking action on their own. They were creating more experiences and knowledge from researching information from different sources, discussing knowledge together in groups, and presenting the project results came with an increase in the improvement score. 3) The excellent learning achievement scores from the four cooperative and collaborative learning activities projects were 83, 89, 91, 99, respectively, and the multiple-choice learning achievement in content was over 80%. 4) The overall satisfaction score of the students through cooperative and collaborative learning through the project work was at a high level, the score of 4.38. Most of the students have continually developed group work skills. There has been a change in behavior in a better direction. Including having a good group working attitude by increasing; as a result, students are satisfied with teaching and learning and have good grades by using cooperative and collaborative learning method.